“A Perfect Place to Die”: Thinking the EcoGothic, Darkness, and the Dark Sweet in Gus Van Sant’s The Sea of Trees - Chang, Kathryn Yalan (SARE: Southeast Asian Review of English, 2022)
Located at the foot of Mountain Fuji in Yamanashi Prefecture, Japan’s gothic forest Aokigahara Jukai, is an (in)famous “suicide forest.” Drawing on Timothy Morton’s three threads pertaining to dark ecology and Elizabeth Parker’s notion of “ecoGothic,” both of which open up a more comprehensive perspective of the dark forest, this article argues that the analysis of Van Sant’s film The Sea of Trees (2015) on Aokigahara brings into question the stereotype of the horrible suicide forest for it not only invokes Morton’s sense of (dark-sweet) meditative space for people to ponder the meaning of life but also brings us to recognize the re-enchantment of the Gothic forest where the strangers have been encountered. This article is divided into four parts: (1) Thinking the EcoGothic; (2) Thinking Darkness; (3) Thinking Dark Sweet; and (4) Conclusion. In my reading, Van Sant’s film cautions us against the stigmatization of the Sea of Trees, exclusively challenging anthropocentrism, calls for a more nuanced aesthetic and spiritual perspective about Aokigahara.